2005
DOI: 10.1128/aac.49.1.57-70.2005
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Active Fungicidal d -Peptide Inhibitors of the Plasma Membrane Proton Pump That Block Azole Resistance

Abstract: Cationic peptides produced by multicellular organisms are an evolutionarily ancient and rapidly mobilized primary defense against infections caused by a broad range of microbes (8). The cationic antimicrobial peptides are ribosomally synthesized, proteolytically processed species of 12 to ϳ50 amino acids that comprise about 50% hydrophobic residues and that have a net excess of positive charge (9). They are usually found on epithelial cell surfaces and in phagocytic cells at sites of microbial invasion, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 41 publications
5
59
1
2
Order By: Relevance
“…However, the inhibition of PI uptake with the peptides tested was not as pronounced as the Hst 5-induced membrane permeability to PI in CaTK1 cells, indicating that the requirement of Trk1p for Hst 5 killing is more explicit or that these peptides may have additional or alternative targets. In this regard, it has been shown that the synthetic D-decapeptide BM2 (D-NH 2 -RRRFWWFRRR-CONH 2 ), which has high fungicidal activity, acts as a specific inhibitor of the yeast plasma membrane proton pump Pma1p (19). Interestingly, this peptide was found to possess some similarity in primary structure to other cationic peptides, including the first 9 residues of LFcn 11, which was able to inhibit Pma1p activity as well (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, the inhibition of PI uptake with the peptides tested was not as pronounced as the Hst 5-induced membrane permeability to PI in CaTK1 cells, indicating that the requirement of Trk1p for Hst 5 killing is more explicit or that these peptides may have additional or alternative targets. In this regard, it has been shown that the synthetic D-decapeptide BM2 (D-NH 2 -RRRFWWFRRR-CONH 2 ), which has high fungicidal activity, acts as a specific inhibitor of the yeast plasma membrane proton pump Pma1p (19). Interestingly, this peptide was found to possess some similarity in primary structure to other cationic peptides, including the first 9 residues of LFcn 11, which was able to inhibit Pma1p activity as well (19).…”
Section: Discussionmentioning
confidence: 99%
“…The putative inhibitors enniatin and the milbemycins ␣11, ␣20, and ␤11 were shown previously to have different pump specificities (19). A peptide from a synthetic D-octapeptide compound library (27,30) denoted RC21 has recently been identified as a specific Cdr1p inhibitor (K. Niimi and B. C. Monk, unpublished results), and disulfiram has reported activity against Cdr1p (44). The frequently studied inhibitor FK506 was not included because analysis would be complicated by its known interaction with the calcineurin stress response pathway in yeast (2,12,46).…”
mentioning
confidence: 99%
“…We have used a Saccharomyces cerevisiae heterologous membrane protein hyperexpression system to construct a panel of mutant strains that hyperexpress individual transporter alleles cloned from fungal pathogens (19,23,25). The panel allows functional analysis of membrane transporters that confer resistance to xenobiotics by using simple drug susceptibility and biochemical assays (21,36,37).…”
mentioning
confidence: 99%